(942) Priority Problems in the Growth Process of Developing Countries مشاكل الأولوية في عملية النمو للدول النامية - Joswig (The Institute of National Planning, 2025)
The problems of economic growth are currently being discussed at various levels, as improving living standards depends on the rapid growth of dynamic economic forces. After the breakup of the colonial system, about 60 former colonies gained political independence, but they now face the challenging task of achieving economic independence. The legacy left by colonial powers complicates their efforts to overcome backwardness. This must be done under the leadership of progressive national forces with support from the socialist world.